Pembentukan Karakter Disiplin melalui Kegiatan Kepramukaan di SDN Sahang - Faiz Lihubbil Ahmadi; Risa Alfiyah Ulfa (Social Science Academic, 2025)
In elementary schools, the development of students’ discipline is a problem that affects learning outcomes and behavior. One extracurricular program, the Scouting program, aims to instill discipline through structured assignments, leadership instruction, and teamwork. The purpose of this community service was to determine how Scouting activities at Sahang Elementary School contribute to the development of student discipline and to identify factors that support or hinder this process. The research method used was Participatory Action Research (PAR). This method was chosen based on the principle of actively involving all stakeholders, including children and teachers at Sahang Elementary School, in every stage of the activity, from planning, implementation, evaluation, and follow-up. Data analysis included the reduction, presentation, and drawing conclusions from primary and secondary data. As the results of the study showed, regular student involvement in Scouting activities significantly improved student discipline, including punctuality, responsibility, and the ability to comply with rules. Supporting factors included continuous guidance from teachers and Scout leaders, while obstacles included varying levels of parental support and limited facilities. Overall, schools, parents, and the surrounding community can collaborate with Scouting to instill discipline.